U.S. strategy in Central Asia - V. N. Zemskov (Vestnik MGIMO-Universiteta)
The article considers the questions connected with the strategy of the U.S. in Central Asia, which has long-term character. In this connection, the author notes that successive governments of the USA, the American political and expert community, business circles traditionally in the last twenty years pay particular attention to this region, bringing to secure the U.S. presence in the region the concept of "Big Central Asia".